Clinical Profile and Mycological Profile of Dermatophytosis: A Cross-sectional Study at a Tertiary Care Hospital in Southern India - Venkataravikanth Eddula; Ashok Rao Matety; C. Sravana Deepthi; Sirshendu Chaudhuri; Vidyasagar Pappula (Current Medical Issues)
Background This cross-sectional observational study aimed to analyze the clinical and mycological characteristics of dermatophytosis in patients visiting the outpatient clinic of the department of dermatology at a tertiary care hospital in Telangana. Methodology The study was conducted from November 2017 to July 2019, involving patients clinically diagnosed with dermatophytosis. Data collection included detailed demographic and clinical information and laboratory investigations such as direct microscopy, fungal culture, and hematological examinations. Specimens were collected from skin lesions, nails, and hair, processed using appropriate methods, and subjected to culture and microscopic examination. Descriptive statistics was performed to present the findings. Results A total of 100 participants were recruited, with a median age of 24 years. The majority were male (n = 75, 75%) and students (n = 47, 47%). Most participants (n = 71, 71%) presented with extensive tinea followed by tinea corporis and tinea capitis. Trichophyton mentagrophytes was the most isolated variant (n = 42, 97.7%) among positive cultures. Conclusion Young male populations are the most common victims in this region. The significant number of tinea cases and the high prevalence of T. mentagrophytes underscore the necessity for precise diagnosis and effective management strategies in treating dermatophytosis.